Renoduodenal Fistula Following Penetrating Abdominal Injury. Issue 4 (April 2022) - Hohenleitner, Julien; Yu, Yasong; Gore, Amy; Traupman, Frank; Jackson, Maya; Kunac, Anastasia
Renoduodenal fistula is an uncommon occurrence and usually results as a complication of injury or inflammatory process. Here, we describe a case of renoduodenal fistula formation after traumatic injury via gunshot wound to the abdomen. The patient suffered right renal and ureteral injury, complicated by urine leak, managed by surgery, interventional radiology, and urology. His post-hospital course was complicated by recurrent urinary tract infections and was found to have a renoduodenal fistula 3 months after the initial operation. Patient underwent uncomplicated right nephrectomy and repair of fistula. Etiology, presentation, diagnosis, and treatment options of renoduodenal fistula are discussed.